The Evangelist. - KROLL, ANDY (American Prospect, 2013)
The article profiles Jim Gilliam, the software developer behind the NationBuilder software which he plans to offer to everyone and give ordinary people the means to support and make change. A background of the life of Gilliam, his medical challenges and how his faith in God was renewed through the Internet is provided. It relates the performance of NationBuilder.